Delayed Onset of Inhibition of Return in Visual Snow Syndrome - Foletta, Paige J.; Clough, Meaghan; McKendrick, Allison M.; Solly, Emma J.; White, Owen B.; Fielding, Joanne (Frontiers in Neurology, 2021)
Visual snow syndrome (VSS) is a complex, sensory processing disorder. We’ve previously shown that visual processing changes manifest in significantly faster eye movements towards a suddenly appearing visual stimulus and difficulty inhibiting an eye movement towards a non-target visual stimulus. We propose that these changes reflect poor attentional control and occur whether attention is directed exogenously or endogenously. Irrespective of how attention is captured, competing facilitatory and inhibitory processes prioritise sensory information that is important to us, filtering out that which is irrelevant. A well-known feature of this conflict is the alteration to behaviour that accompanies variation in the temporal relationship between competing sensory events that manipulate facilitatory and inhibitory processes. A classic example of this is the ‘Inhibition of Return’ (IOR) phenomenon that describes the relative slowing of a response to a validly cued location compared to invalidly cued location with longer cue/target intervals. This study explored temporal changes in the allocation of attention using an ocular motor version of Posner’s IOR paradigm, manipulating attention exogenously by varying the temporal relationship between a non-predictive visual cue and target stimulus. Forty participants with VSS (20 with migraine) and 20 controls participated. Saccades were generated to both validly and invalidly cued targets with 67, 150, 300 and 500 msec cue/target intervals. VSS participants demonstrated delayed onset of IOR. Unlike controls, who exhibited IOR with 300 msec and 500 msec cue/target intervals, VSS participants only exhibited IOR with 500 msec cue/target intervals. These findings provide further evidence that attention is impacted in VSS, manifesting in a distinct saccadic behavioural profile. Whether IOR is perceived as the build-up of an inhibitory bias against returning attention to an already inspected location or a consequence of a stronger attentional orienting response elicited by the cue, our results are consistent with the proposal that in VSS, a shift of attention elicits a stronger increase in saccade-related activity than healthy controls. This work provides a more refined saccadic behavioural profile of VSS that can be interrogated further using neuroimaging techniques and may, in combination with other saccadic markers, be used to monitor the efficacy of future treatments.